(untitled) (E Conference Zone, 2024)
Sustained high interest rates in the global economy, conflicts between countries, low rates of international trade, and natural disasters caused by climate change have a significant impact on global economic growth. The global economic growth rate of the world economy is projected to reach 2.4 percent in 2023, which is lower than the 3 percent growth rate recorded before the pandemic in 2024.